ETHNOBOTANY STUDY OF Albizia procera IN TAMIANG HILL FOREST OF TANAH LAUT REGENCY AS A POPULAR SCIENTIFIC BOOK - Nada Salsabila; Dharmono Dharmono; Aminuddin Prahatama Putra (ATRIUM PENDIDIKAN BIOLOGI, 2021)
Birik wood (Albizia procera) grows wild in the Tamiang hill forest and is often used by the local community. This study aims to describe the ethnobotany of the Albizia procera plant in the Tamiang hill  forest area, Tanah Laut Regency and describe the validity and practicality of the contents of the popular scientific book on the Albizia procera plant. The research method used was descriptive research for ethnobotany studies and continued with the formative evaluation of the Tessmer test for the feasibility of the developed popular sciencetific book. The results showed that the Albizia procera plant had tree species, had white round stems, sympodial branches, double pinnate compound leaves, unlimited compound flowers, dry true fruit with pod and taproot type. Albizia procera plant is used as stomachache medicine, also used for road shade and livestock feed. The Albizia procera plant is believed by local people if it is burned it will cause the goat hair to fall out. Albizia procera plants are widely used as firewood, building materials and food materials. People in the hill forest area of Tamiang call the Albizia procera plant "birik wood" because of its speckled stems. The results of the development of teaching materials in the form of Popular Scientific Books on expert tests by 2 validators had very valid results, and the practicality of the content by 3 students had very good results. This popular scientific book is to support the Ethnobotany subject.